PENINGKATAN PENGUASAAN MATERI PEMBELAJARAN IPS TENTANG USAHA DAN KEGIATAN EKONOMI MELALUI MODEL PEMBELAJARAN KONSTRUSTIVISME SISWA KELAS V SEKOLAH DASAR NEGERI 1 SELATPANJANG SEMESTER 1 TAHUN PELAJARAN 2018/2019 - Samikam Samikam (Jurnal Guru Kita PGSD, 2020)
Abstract: Improvement of Mastery of Ips Learning Materials on Business And Economic Activities Through The Model of Learning Confidivism of Grade V Students of State Elementary School 1 Selatpanjang Semester 1 Year Of Study 2018/2019. This research aims to improve the learning process, activeness and learning outcomes of students by applying a model of constructivism. The subject of his actions was grade V students of SDN 1 Strait long Tebing Tinggi Sub-District of Meranti Islands District which consisted of 14 male students and 8 female students. The research method used in this study is Class Action Research (PTK) which starts from planning, implementation, observation and reflection. The study was conducted in two cycles. As for the instrument of data collection in the form of cycle tests, the observation sheet. Tests are used to determine the student's learning outcomes after the implementation of learning actions, the observation sheet of teachers / researchers and students is used to observe the improvement of student learning activity. Data collection techniques using observation techniques, tests and documentation. Data validation uses techniques to extend observation, continuous observation, and triangulation. The method of data analysis in this study uses qualitative data analysis. The results found that students' learning outcomes after learning actions improved. The data showed that in the early stages of student learning activity by 38.46% or 5 students increased to 76.92% in the first cycle or as many as 10 students, and in the second cycle to 100% or as many as 13 students were declared complete. The explanation of learning outcomes and learning outcomes was shown by an increase in average learning outcomes from 56.92 to 65.38 in the first cycle, and in the second cycle to 73.08 as well as an increase in learning completedness from 3 students or 23.08% to 8 students or 61.54% and 12 students or 92.31% in the second cycle. The conclusion is that through the model of constructivism learning can improve the learning process, activeness and learning outcomes of grade V students of SDN 1 Strait long Tebing Tinggi Sub-District of Meranti Islands Regency in Semester 2 of the Year 2018/2010. Keywords :, Activeness, Learning Outcomes, ConstructivismAbstrak: Peningkatan Penguasaan Materi Pembelajaran Ips Tentang Usaha Dan Kegiatan Ekonomi Melalui Model Pembelajaran Konstrustivisme Siswa Kelas V Sekolah Dasar Negeri 1 Selatpanjang Semester 1 Tahun Pelajaran 2018/2019. Penelitian ini bertujuan untuk meningkatkan proses pembelajaran, keaktifan dan hasil belajar siswa dengan menerapkan model konstruktivisme. Subjek yang dikenai tindakanya itu siswa kelas V SDN 1 Selat panjang Kecamatan Tebing Tinggi Kabupaten Kepulauan Meranti yang 22 siswa terdiri dari siswa laki-laki sebanyak 14 siswa dan siswa perempuan sebanyak 8 siswa. Metode penelitian yang digunakan dalam penelitian ini yaitu Penelitian Tindakan Kelas (PTK) yang dimulai dari perencanaan, pelaksanaan, observasi dan refleksi. Penelitian ini dilakukan sebanyakduasiklus. Adapun instrument pengumpulan data berupatessiklus, lembarobservasi. Tes digunakan untuk mengetahui hasil belajar siswa setelah pelaksanaan tindakan pembelajaran, lembar observasi guru/ peneliti serta siswa digunakan untuk mengobservasi peningkatan keaktifan belajar siswa. Teknik pengumpulan data menggunakan teknik observasi, tes dan dokumentasi. Validasi data mengunakan teknik memperpanjang masa observasi, pengamatan yang terus menerus, dan triangulasi. Metodeanalisis  data dalam penelitian ini menggunakan analisis data kualitatif. Hasil penelitian ditemukan bahwa hasil belajar siswa setelah dilakukan tindakan pembelajaran mengalami peningkatan. Data menunjukkan bahwa pada kondisi awal keaktifan belajar siswa sebesar38,46% atau 5 siswa meningkat menjadi 76,92% pada sikluspertamaatausebanyak 10 siswa, dan pada sikluskeduamenjadi 100%  atausebanyak 13 siswa dinyatakan tuntas. Adapun penjelasan mengenai hasil belajar dan ketuntasan belajar ditunjukkan dengan peningkatan nilai rata-rata hasil belajar dari sebesar 56,92 menjadi 65,38 pada siklus pertama, dan pada siklus kedua menjadi 73,08 serta peningkatan ketuntasan belajar dari 3 siswa atau 23,08% menjadi 8 siswaatau 61,54% dan 12 siswaatau 92,31% pada siklus kedua. Kesimpulannya bahwa melalui model pembelajaran konstruktivisme dapat meningkatkan proses pembelajaran, keaktifan dan hasil belajar siswa kelas V SDN 1 Selat panjang Kecamatan Tebing Tinggi Kabupaten Kepulauan Meranti  pada Semester 2 Tahun Pelajaran 2018/2010. Kata Kunci :, Keaktifan, Hasil Belajar, Konstruktivisme